Unilateral and Bilateral Lower-Body Resistance Training Does not Transfer Equally to Sprint and Change of Direction Performance. Issue 1 (January 2020) - Appleby, Brendyn B.; Cormack, Stuart J.; Newton, Robert U.
Abstract : Abstract: Appleby, BB, Cormack, SJ, and Newton, RU. Unilateral and bilateral lower-body resistance training does not transfer equally to sprint and change of direction performance. J Strength Cond Res 34(1): 54–64, 2020—Given maximal strength can be developed using bilateral or unilateral resistance training, the purpose of this study was to determine the magnitude of transfer of unilateral or bilateral resistance training to sprint and change of direction (COD) performance. Thirty-three trained participants (average training age = 5.4 ± 2.9 years and 1 repetition maximum [1RM] 90° squat = 177.6 ± 26.7 kg) completed either a bilateral group (BIL, n = 13), unilateral (UNI, n = 10), or comparison (COM, n = 10) 18-week randomized controlled training design. Training involved 2 lower-body, volume-load–matched resistance sessions per week (6–8 sets × 4–8 reps at 45–88% 1RM), differing only in the prescription of a bilateral (squat) or unilateral (step-up) resistance exercise. Strength was assessed through 1RM squat and step-up, in addition to 20-m sprint and a customized 50° COD test. The effect size statistic ± 90% confidence limit (ES ± CL) was calculated to examine the magnitude of difference within and between groups at each time point. BIL and UNI groups improved their trained and nontrained strength exercise with an unclear difference in adaptation of squat strength (ES = −0.34 + 0.55). Both groups improved 20-m sprint (ES: BIL = −0.38 ± 0.49 and UNI = −0.31 ± 0.31); however, the difference between the groups was unclear (ES = 0.07 ± 0.58). Although both groups had meaningful improvements in COD performance, bilateral resistance training had a greater transfer to COD performance than unilateral resistance training (between-groups ES = 0.59 ± 0.64). Both bilateral and unilateral training improved maximal lower-body strength and sprint acceleration. However, the BIL group demonstrated superior improvements in COD performance. This finding potentially highlights the importance of targeting the underlying physiological stimulus that drives adaptation and not exercise selection based on movement specificity of the target performance.